Aspects of the biology of climbers in southern Africa - Balfour, David Andrew (Department of Biological Sciences, 2016)
This study examines factors that may limit the abundance and distribution of climbers and the influence that climbers may have on the regeneration of forests. The abundance of climbing plants (climbers) was established over a soil nutrient gradient, under standardised light conditions. Abundance was found to be positively correlated with the potassium concentration and the soil S-value, but not with other nutrients. Thus, the association between climbers and soil nutrient levels is challenged. Instead the abundance of climbers was found to be positively correlated with tree canopy architecture and trellis availability. More climbers entered host trees with low canopies (< 15 m) than those with high canopies. Trees with low canopies had more climbers entering vertically into the canopy while trees with high canopies had more climbers entering the canopy horizontally. Evidence was found to suggest that climbers facilitate the entry of each other into tree canopies. Tree and climber saplings were grown under three nutrient and two light treatments to compare the relative growth rates of their terminal shoots under the different conditions. While climbers were found to have greater shoot extension rates than trees, they did not grow relatively faster than trees under any of the combination of treatments. Thus light levels and soil nutrient availability may not influence the competitive ability of climbers compared to trees. Three aspects of the carbon gain capacity (maximum photosynthetic rate, leaf nitrogen concentration and leaf water use efficiency) were compared between climbers and trees. While the climbers had a significantly higher leaf nitrogen concentration than trees, as well as higher leaf water use efficiency; the maximum carbon assimilation rates of climbers and trees did not differ. These differences between trees and climbers are slight and suggest that differences in growth rates between the two growth forms are largely due to differences in carbon allocation in trees (to support structures) and in climbers (shoot elongation), rather than carbon gain mechanisms. Patterns of canopy tree regeneration in gaps and sub-canopy plots were determined for lowland and highland forests to determine whether climbers influenced the regeneration of canopy trees. More canopy trees regenerate in the sub-canopy of highland forests, while in lowland forests treefall gaps are the major sites of canopy tree regeneration. These patterns of regeneration were found not to be related to the density of the ground layer, the extent of the lateral infill of the gap-forming trees or the abundance of woody climbers. Instead, a negative correlation was found between the percentage of regenerating canopy species and the density of the herbaceous and shrubby understory layer in both lowland and highland forests. Thus in both forests the understory layer has an important influence on the regeneration of canopy trees. The role of vertebrate herbivores may be important in providing the necessary release from suppressive effect of the dense understory layer and to enable the regeneration of canopy tree species in the lowland forests.